Profiles and predictors of resilient functioning in youths with pediatric cancer history. Issue 4 (13th July 2021) - Okado, Yuko; Long, Alanna; Phipps, Sean
Abstract: Objective: To identify and predict resilient functioning over time among youths with pediatric cancer experience (YPCE). Design: YPCE aged 8–17 years ( N  = 231) were followed prospectively for 3 years. Their psychosocial adjustment was assessed using self-report and parent-report at 1 year (T2) and 3 years (T3) post-baseline. Methods: Latent profile analysis identified subgroups of YPCE with different patterns of adjustment over time. Self-reported factors from baseline and T2 were examined as predictors of subgroup membership. Findings: Three subgroups of youths were found. Two exhibited average (52.5% of the sample) to better-than-average (41.3%) functioning. One subgroup (6.2%) exhibited subclinical but at-risk range of adjustment. Low optimism and low connectedness to parents and school predicted membership in this group. Conclusions: Most YPCE exhibit resilient functioning across time. However, approximately 6% report persistent maladjustment. Implications: Most YPCE are well-adjusted, but those with low optimism and poor connection to parents or school may require monitoring for psychosocial difficulties.